Synthesis of new quinolizinium-based fluorescent compounds and studies on their applications in photocatalysis. Issue 39 (20th September 2021) - Yip, Wai-Ming; Yu, Qiong; Tantipanjaporn, Ajcharapan; Chan, Wing-Cheung; Deng, Jie-Ren; Ko, Ben Chi-bun; Wong, Man-Kin
Abstract : A new library of quinolizinium compounds was synthesized via Rh catalyzed C–H bond functionalization. Systematic studies on their photophysical properties and applications in photoredox catalysis have been conducted. Abstract : Quinoliziniums, cationic aromatic heterocycles bearing a quaternary bridgehead nitrogen, have been widely used as fluorescent dyes, DNA intercalators, ionic liquids etc . A library of new quinolizinium compounds was synthesized from quinolines and internal alkyne substrates in up to 65% isolated yields. Systematic studies of their photophysical properties were conducted. The quinoliziniums have been used in three visible-light-induced photocatalysis reactions with good yields.